Quality diversity of 35 tea clones (Camellia sinensis var. sinensis) processed for green tea (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Prayoga MK, Syahrian H, Rahadi VP, Atmaja MIP, Maulana H, Anas. 2022. Quality diversity of 35 tea clones (Camellia sinensis var. sinensis) processed for green tea. Biodiversitas 23: 810-816. The development of sinensis clones in Indonesia is still focused on increasing productivity and until now there has been no study on the level of genetic similarity and diversity based on quality characters. Therefore, the purpose of this study was to examine the level of kinship and genetic diversity of 35 sinensis clones from the collection of the Indonesia Research Institute for Tea and Cinchona. The study consisted of two stages, testing the content of chemical compounds (polyphenols and caffeine) and organoleptic testing. The material used in both tests was fresh shoots consisting of peko + 3 young leaves (P+3). In organoleptic testing, shoots of 35 sinensis variety clones were first processed into green tea. Furthermore, the processed green tea was tested organoleptically by three credible panelists. The data from the test results of chemical and organoleptic compounds were then tested statistically to get the coefficient of variation (CV), which indicates data diversity. The level of genetic closeness between clones based on quality characters was analyzed using the JMP 16.0 program (trial version), then arranged into clusters. To see the contribution of each parameter to the quality diversity of 35 sinensis clones, a principal component analysis (PCA) was carried out. The results of this study indicate that there are four main clusters grouping the 35 sinensis clones tested. The first cluster excels in the character of taste and aroma, the second cluster excels in appearance, seductive colour, and infusion, the third cluster excels in the character of polyphenols, while the fourth cluster excels in the character of caffeine. The characters that contributed to the genetic diversity of the 35 clones tested were caffeine, appearance, and aroma.
Keywords: cluster analysis, green tea, principal component analysis, quality character, and Sinsneis clone